Comparação de diferentes testes funcionais e suas relações com estado funcional e qualidade de vida em indivíduos com doença pulmonar obstrutiva crônica (DPOC) - Pessoa, Bruna Varanda (2008)
Objectives: to evaluate and compare the responses to the various functional tests, and the concordance between the six-minute walk test in hallway (6MWT) and the of oval track (6MWToT), of treadmill (6MWTT), and of treadmill with inclination (6MWTTI), the six-minute step test (6MST) and the two-minute chair test (2MCT), in patients with Chronic Obstructive Pulmonary Disease (COPD), and to correlate the responses with functional state and quality of life. Methods: Ten patients with COPD (72±7years, 30%<FEV1<80%predicted) were assessed using the functional tests. A dyspnea was assessed using the London Chest Activity of Daily Living and the Medical Research Council scales; and the quality of life was assessed using the St George s Respiratory Questionnaire (SGRQ). Results: In the interests analysis, there was lower walking distance in the 6MWTT and 6MWTTI was observed, to compare in the 6MWT and 6MWToT; the ∆Sp,O2 (delta of arterial oxygen saturation measured by pulse oximeter) in the 6MWTTI was significantly greater that in the 6MWT, but not between to change in dyspnea and fatigue/pain in the lower-limbs between rest and exercise of peak (∆). Concordance and correlation was observed between the lower Sp,O2 of the 6MWT with the 6MWToT, 6MWTT, 6MWTTI, 6MST and 2MCT. Strong correlations was observed between the performances on the 6MST and 6MWT, 6MWToT and 6MWTT; and between the physical activity domain of the SGRQ with the performances in the 6MWT, 6MWToT, 6MWTT, 6MST and 2MCT. Conclusion: The functional tests produced similar subjective responses; however, the 6MWTTI caused greater desaturation that 6MWT. The concordance between the 6MWT and the tests performed, suggests acceptable use of any these tests in the physiotherapeutic clinical routine of the individuals COPD. The tests performed, except the 6MWTTI, shown to be indicators of the quality of life (physical activity domain)